High levels of energy expenditure in obese women. Issue 6526 (12th April 1986) - Prentice, A M; Black, A E; Coward, W A; Davies, H L; Goldberg, G R; Murgatroyd, P R; Ashford, J; Sawyer, M; Whitehead, R G
Abstract : Total free living energy expenditure was compared in lean and obese women by the new doubly labelled water method and partitioned into basal metabolism and thermogenesis plus activity by whole body calorimetry. Average energy expenditure was significantly higher in the obese group (10.22 versus 7.99 MJ/day (2445 versus 1911 kcal/day); p less than 0.001) resulting from an increase in the energy cost of both basal metabolism and physical activity. Self recorded energy intakes were accurate in the lean subjects but underestimated expenditure by 3.5 MJ/day (837 kcal/day) in the obese group. Basal metabolic rate and energy expenditure on thermogenesis plus activity were identical in the two groups when corrected for differences in fat free mass and total body mass. In the obese women in this series there was no evidence that their obesity was caused by a metabolic or behavioural defect resulting in reduced energy expenditure.